Performance Study of Micro, Small and Medium Enterprises (MSMEs): Case Study of Economic Value Added Method and Financial Decision - Laksmana, Komang Agus Rudi Indra (East Asian Journal of Multidisciplinary Research, 2024)
This research provides empirical evidence for developing the concept of measuring financial performance with EVA proxies in the MSME sector. This study uses a quantitative research design based on the positivism paradigm. The sample size used in this study was the Slovin formula. The calculation results show that the number of samples was 211.76 or rounded to 212 samples. The results of this study also found financial decisions have a positive and significant effect on financial performance. MSMEs can use the financial component of the EVA, which is available directly from their accounting information, coupled with the activities of the organization affecting it, to identify areas where it can create value.